A portable biosensor for simultaneous diagnosis of TNF-α and IL-1β in saliva biomarkers using twin electronic devices - Monajjemi, M.; Mollaamin, F.; Dehghandar, M.; Shahriari, S.; Latifi, P.; Mohammadi, S. (Copernicus GmbH, 2024)
Abstract. For several types of diseases, such as meningitis or oral cancers, the simultaneous diagnosis and measurement of the tumour necrosis factor α (TNF-α) and interleukin-1 β (IL-1β) immune-modulating biomarkers, with respect to both quality and quantity, are important. For example, although meningitis is generally caused by bacteria or viruses, the differences between viral and bacterial structures can be problematic for medical doctors to distinguish, as laboratory data assay techniques for the two are often similar and can overlap; moreover, in such cases, distinguishing between virial and bacterial structures is especially problematic following the use of antibiotics prior to cerebrospinal fluid testing. In this work, we simultaneously evaluated the precision of both TNF-α and IL-1β for the diagnosis of disease. In this research area, twin electrochemical biosensors have been designed as strong tools for the wide-spectrum assessment of biomarkers, thereby aiding in the screening, diagnosis, and monitoring of pathologies and treatment performance. In this research, we present a sensor platform model that can enable one to detect biomarkers quickly; specifically, this platform can be used to detect TNF-α and IL-1β in saliva. A two-peptide recognition element was created and designed using the phage display technique. This element selectively binds TNF-α and IL-1β to an electronics-based metal–oxide–semiconductor field-effect transistor/electrolyte-gated transistor (MOSFET/GT) bio-detector device and label-free biosensor, allowing for the rapid, simultaneous detection of both biomarkers. These bio-affinity recognition methods have been successfully implemented to realize the experimental twin-model sensor, based on electrolyte-gated transistor (EGT) and semiconductor field-effect transistor (ZnO-SFET) biosensors, to test for these two disease biomarkers, both individually and simultaneously, with high performance. In summary, we developed a sensor platform that can be used for rapid oral cancer signature analysis of biomarkers in multiple bio-fluids of saliva. This system works by arraying metal–oxide–semiconductor field-effect transistors (MOSFETs), with each targeting a biorecognition element (BRE) specific to one of these two important biomarkers. This system can also be extended upon to aid in a wide variety of cancer research applications.
Keywords: Technology; T